Sudbury, Ontario, and the Meteorite Theory - Stevenson, John; Stevenson, Louise (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1980)
Summary The origin of the Sudbury Basin, Onta-rio, has been the subject of much con-troversy, and the controversy was reacti-vated for further discussion in the 1960swhen Dietz proposed the meteoritetheory. The proof of the Sudbury astro-bleme has depended largely on shattercones in the area and on planar featuresdetailed microscopically in quartz insome rocks. Literature is cited to showthat such evidence is not in itself proofof origin of meteorite impact. Also ques-tioned is whether the Sudbury ore camefrom outer space or from the Earth. Theunique geological setting of Sudbury,near the junction of the threeprovinces of the Canadian Shield,is also considered in relation to themeteorite theory.